Determinação da variação do fator de perda de carga em sistemas fluido mecânicos por ação de bio incrustantes, o caso do Limnoperna Fortunei: uma correlação com o tempo de operação desses sistemas - Tâmara Rita Costa de Souza (2016)
Brazil has in its energy matrix a large share of hydroelectric generation, this portion that for some time been suffering from the impacts caused by the infestation of Limnoperna fortunei, popularly known as golden mussel. This mollusk is an invasive species coming from South Asia, detected in South America in 1991 in Rio de La Plata and since then its traces are found along the entire coast as well as ports and rivers throughout Brazil. This type of mussel, and affect the fauna and local flora has been causing problems through its scale in pipes and conduits of the entire hydroelectric network and also domestic. Its clamping often causes clogging of pipes with smaller diameters and in other cases a reduction of the internal diameter of the pipe, which carries a pressure loss increases. There are several studies on how to control the infestation of the species, but until now there is still no reports of any process eradicated or contained such infestation. This paper presents an assessment of the effect on fouling of pipes with different diameters being possible to determine the evolution of the pressure loss factor due to the infestation, varying according to the number of layers of fouling. The results show that the smaller the pipe, the greater the impacts related to losses and efficiency, both compared to systems without any fouling. In many cases you can have problem of occlusion of the pipes, causing system clogging. For larger diameters, the impact is correspondingly smaller. However, as the number of scaling layers increases there is an increased pressure drop in the system. Importantly, the mollusk study presents high rates of infestation and can survive, develop and grow under different conditions, requiring new and constant comments about their progress on the watersheds in Brazil.